2011
DOI: 10.1007/s12243-011-0254-y
|View full text |Cite
|
Sign up to set email alerts
|

An analytical model for jitter in IP networks

Abstract: Traditionally, IP network planning and design is mostly based on the average delay or loss constraints which can often be easily calculated. Jitter, on the other hand, is much more difficult to evaluate, but it is particularly important to manage the QoS of realtime and interactive services such as VoIP and streaming video. In this paper, we present simple formulas for the jitter of Poisson traffic in a single queue that can be quickly calculated . It takes into account the packets delay correlation and also t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 15 publications
0
17
1
Order By: Relevance
“…The values of delay and jitter produced by the problem (18-24) are higher comparing with those provided, respectively, by the problems (7)(8)(9)(10)(11) and (12)(13)(14)(15)(16)(17). Therefore, even if the optimization does not provide a best solution for both delay and jitter, it produce a compromise between this two performance measures.…”
Section: Our Proposed Models Comparisonmentioning
confidence: 91%
See 2 more Smart Citations
“…The values of delay and jitter produced by the problem (18-24) are higher comparing with those provided, respectively, by the problems (7)(8)(9)(10)(11) and (12)(13)(14)(15)(16)(17). Therefore, even if the optimization does not provide a best solution for both delay and jitter, it produce a compromise between this two performance measures.…”
Section: Our Proposed Models Comparisonmentioning
confidence: 91%
“…In this study, we consider the delay and jitter model for Poisson traffic developed in [7]. The purpose of this work is to produce a simple formula for the end-to-end delay and jitter of Poisson traffic in a single queue and then extend the model for multiple queues defining a path.…”
Section: B Analytical Delay and Jitter Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In both cases, low QoE/QoS values are expected. It has been shown that jitter actually improves as the load ρ increases and that the jitter on a path depends on where the more congested links occur on that path, which is in strong contrast with other QoS measures such as delay or packet loss …”
Section: Fiwi Access Network Traffic Optimizationmentioning
confidence: 99%
“…In further analysis, it is considered that the arrival rate of the tagged flow takes values between these two extreme points . If the arrival process is given as Poisson λ k and under the assumption of intermediate arrival rate, the end‐to‐end jitter of a tagged flow produced by a single node can be approximated as presented in expressions , and . Jks=1ηsfalse[1eηsτkfalse(ηsτk+eηsτkfalse)false], Jkr=1ηrfalse[1eηrτkfalse(ηrτk+eηrτkfalse)false], JkD=1ηDfalse[1eηDτkfalse(ηDτk+eηDτkfalse)false]. …”
Section: Fiwi Access Network Traffic Optimizationmentioning
confidence: 99%